(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates the role of Resource Consumption Accounting (RCA) in improving cost accuracy and supporting sustainable competitive advantage (SCA) in the cement industry of the Kurdistan Region, Iraq. Using empirical cost data from a leading cement company, the study compares unit costs of Ordinary Portland Cement (OPC), Sulphate-Resisting Cement (SRC), and Pozzolanic Block Cement (PBC) under traditional costing and RCA systems. The analysis shows substantial differences, with RCA increasing OPC costs while reducing SRC and PBC costs, yielding potential annual savings exceeding 8.6 billion IQD and directly enhancing the cost dimension of SCA. While direct evidence for innovation, quality, and delivery improvements was not captured, managerial insights indicate that these savings can be strategically reinvested to improve production flexibility, quality control, and responsiveness. Framed within the Resource-Based View and Dynamic Capabilities perspectives, the findings highlight RCA’s role as a strategic resource, emphasizing its potential to drive broader organizational capabilities, guide pricing and capacity decisions, and strengthen competitiveness across multiple dimensions. These findings demonstrate that RCA is not merely a costing tool but a strategic enabler, capable of transforming financial insights into actionable decisions that enhance efficiency, flexibility, and long-term competitiveness in emerging-market industries.